Effect of distinct warm up routines on torque production and range of motion in young males - Brentano, Michel Arias; Rodrigues, Luciana Pestana; Kruel, Luiz Fernando Martins (Brazilian journal of physical education and sport, 2008)
Stretching exercises are commonly included in warm-up routines before resistance exercises. However, some authors suggest that stretching exercises may affect negatively activities that require maximal strength. The purpose of this study was to verify the impact of three different warm-up sessions on hip range of motion (ROM), peak torque and total work of right knee flexors of young adults. Ten trained men without neuromuscular injury were tested isocinetically at three velocities (60°/s, 90°/s and 120°/s) after different warm-up sessions: stationary bike (B), stationary bike and static stretch (S), stationary bike and "hold-relax" technique (FNP). The right hip ROM variation after warm-up sessions was obtained with a goniometer. Comparisons were made with analyses of variance (ANOVA) for repeated measures and post-hoc Bonferroni (p ≤ 0.05). Our results showed a peak torque reduction in FNP session at the concentric phase, compared with S session at velocity 60°/s (S: 182.4 + 24.5 Nm vs. FNP: 168.5 + 27.8 Nm) and B session at velocity 120°/s (B: 141.4 + 15.9 Nm vs. FNP: 129.2 + 18.4 Nm). The FNP session promoted a higher range of motion variation when compared with E session. (E: 18.3 + 10.9 degrees vs. FNP: 27.9 + 6.8 degrees). We concluded that FNP stretching exercises may promote a negative effect on maximal force of knee flexors, while static stretching exercises promotes no negative effect. However, to increase the hip ROM , the "hold-relax" FNP technique seems to be a better choice.